PENGARUH PROMOSI, REPUTASI DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI MINI MARKET TWANK GRASS SRAGEN - Rima Parawati Bala; Septiana Novita Dewi; Ayu Merri Lusiana (STIE Atma Bhakti, 2022)
The purpose of this study was to determine empirically the effect of promotion, reputation and location on purchasing decisions at the Twank Grass Mini Market Sragen. The population in this study were consumers at the Twank Grass Mini Market Sragen with a total of 220 consumers in the first week of October 2021. And the samples taken in this study were 30% of the population, namely 220x30% = 66 respondents and then rounded up to 70 respondents. With a simple random sampling technique. The analysis technique in this research consists of instrument testing: validity & reliability test, classical assumption test, multiple linear regression analysis, t test, F test and R2 test (coefficient of determination test). The results of the regression test can be seen that promotion, reputation and location have a positive effect on consumer purchasing decisions. reputation variable is the most dominant variable because it has the highest regression coefficient value. The t-test results show that promotion, reputation and location partially have a significant effect on the consumer purchasing decision variables. The results of the F test can be concluded that promotion, reputation and location variables have a significant influence on consumer purchasing decisions at the Twank Grass Mini Market Sragen.